t-BHQ Protects Against Oxidative Damage and Maintains the Antioxidant Response in Malnourished Rats - Graciela Gavia-García; María de los Ángeles Rosas-Trejo; Eduardo García-Mendoza; Rafael Toledo-Pérez; Mina Königsberg; Oralia Nájera-Medina; Armando Luna-López; María Cristina González-Torres (SAGE Publishing, 2018)
Objective: Tert-butylhydroquinone (t-BHQ) protective effect against oxidative damage in thymus from malnourished pops-rats was evaluated. Methods: Malnutrition in pops-rats was induced during the lactation period and first-, second-, and third-degree malnourished rats were studied (MN1, MN2, and MN3). To determine t-BHQ protective effect, lipid peroxidation (LPx) was assessed, as well as the carbonyl content. The reduced glutathione and glutathione disulfide content were determined and antioxidant enzyme activities were measured. Results: Oxidative protein damage, LPx, and Nuclear Factor-κB (NF-κB) content, increased in the MN2 and MN3 compared to well-nourished rats, associated with lower protein content and antioxidant activity of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase. Tert-butylhydroquinone treatment induced a protective effect against lipids and proteins oxidative damage, as well as decrease in NF-κB in MN rats and restored the antioxidant mechanisms, mostly GPx and SOD. No differences were found between male and female animals. Conclusions: Results show that higher body weight deficit leads to increased oxidative damage and probably inflammation, attributable to alterations in antioxidant mechanisms. These effects were reversed by the t-BHQ-treatment, which restores the antioxidant response. Our findings suggest that t-BHQ could be an interesting pharmacological intervention, but it needs to be studied further.